Increasing urban health awareness using an interactive approach: evidence from a school-based study: Doris Zjalic. (25th October 2022) - Zjalic, D; Nachira, L; Lanza, TE; Perilli, A; Paladini, A; Santoli, G; Heidar Alizadeh, A; Ricciardi, W; Moscato, U; Cadeddu, C
Abstract: Issue: Urbanization is a cause of climate change, as cities are where these changes are most visible. Climate change also leads to significant inequalities and health issues in urban settings. In this context, urban health promotion is mandatory to increase adaptive capacity. Since the late 1980s the World Health Organization (WHO) has emphasized schools' role in promoting health, as they can play a crucial role in increasing health awareness to future urban inhabitants. Description: The objective of this pre/post-interventional study is to measure the awareness of urban health and green spaces among high school students and to rise it through an educational intervention. Four interactive sessions were delivered to 319 students from 13 to 18 years old in a high school in Rome, Italy during spring 2022. Data was gathered anonymously and analysed using descriptive and inferential statistics. Results: A total of 192 (60%) students successfully completed the pre/post-intervention surveys. An increase in students' knowledge of urban health and urban green areas was observed. Before the intervention 11.8% of participants were aware of urban health, whereas after the intervention 87.5% were aware. A rise across different areas appeared to be related to how many times the teachers repeated that concept during the intervention. For topics discussed in more than one session, the increase in correct answers averaged 13.9%. Two different trends emerged from the data analysis: one whose post-intervention test improved on most of questions and one whose post-intervention test remained unchanged. Lessons: The results of the present study suggest that school-based interventions using interactive approaches on climate change and urban health are effective for increasing the knowledge level of scholars on these topics, and can be a useful way to promote health in an urban setting. This type of approach maintains high levels of concentration and interest in most students. Key messages: Urban health training activities in schools are needed to empower youth who live in urban settings. Interactive sessions keep student concentration high and improve their participation.